Influence of the dry and rainy periods on clinical parameters in canindé and moxotó goats - Xavier Eloy, Ângela Maria; De Aguiar, Francisco Cavalcante; Pinheiro, Raymundo Rizaldo; Silva, Nadiana Maria Mendes; De Brito, Roberta Lomonte Lemos [UNESP]; De Araújo, Adriana Mello; De Brito, Ismeânia França; Furtado, João Ricardo (My University, 2011)
Goats have a thermoregulatory system which maintains a constant body temperature within certain limits regardless the room temperature. When these limits are established, they are used in various physiological mechanisms maintaining body temperature within normal limits. Thus the animal production may fall due to thermal stress caused by high temperatures, especially in tropical areas like Northeast of Brazil. This work aimed to evaluate the physiological behavior from different goats genetic groups through physiological answers of rectal temperature (RT), respiratory frequency (RF), heart beat (HB) and ruminal movements (RM) and also to establish the physiological values for these breeds under semi arid conditions from Northeast of Brazil. It was randomly selected 30 animals, five males and ten females Canindé and five males and tenfemales Moxotó breed. It was obtained the HB, RF and RT in April and September/2007 and 2008. It was observed a significant influence (P<0.05) of the period of the year on HB, RF and RT in Canindé breed, being observed higher values of HB and RT in the rainy period. In Moxotó it was observed a significant difference (P <0.05) in HB and RT between the periods studied, being observed in the dry season the highest HB and RT. The correlation between air temperature (AT) and RT was negative (47%) in the dry period to Moxotó, whereas in the rainy season the correlation was positive (28%). Also the correlation between AT and HB was negative (21%) in the rainy period and positive (25%) in the dry season. In Canindé breed it was observed negative correlation (39%) between AT and RM in the rainy season, while in the dry period this correlation was positive (33%). According to this study the clinical parameters are within the normal range for the goat specie in the Northeast semi-arid and the Moxotó breed showed a pattern consistent with better tolerance to the regional climate and a higher degree of adaptability.
Influeância dos períodos, seco e chuvoso, sobre os parâmetros clínicos em caprinos das raças canindé e moxotó
Keywords: Semi arid region; Small ruminants; Thermoregulation